TYRPLAGERI? - Rifbjerg, Klaus (Tidsskriftet Antropologi, 1996)
Klaus Rifbjerg: Tor(o)menting Written as “reflections on the strange sport of bull-fighting by a relatively civilised Dåne”, the article begins by discussing the unavoidably heated character of arguments, used by any reasonable person against cruelty to animals. Therefore it would be impossible to defend bull-fighting if it did not, as its core, have other meanings, albeit meanings hard to grasp. At least one has to notice the subtle aesthetic aspects - the stylistic variations of movements, the improvisations exploitable under an invariable observation of very strict mies, etc. - that combine to make the fight between man and beast into a very serious ritual of life and death. If one can’t appreciate this playing on forms inside forms, one will never get close to the symbolic content of one man’s playful slaughter of the prototypical animal of natural power: allowing us vicariously to experience a ritual escape from what we most dreadfully fear, the death in death.